Recent advances in photothermal therapy-based multifunctional nanoplatforms for breast cancer - Sun, Jingjun; Zhao, Haiyan; Xu, Weixuan; Jiang, Guo-Qin (Frontiers in Chemistry, 2022)
Breast cancer (BC) is one of the most common cancers in women worldwide; however, the successful treatment of BC, especially triple-negative breast cancer (TNBC), remains a significant clinical challenge. Recently, photothermal therapy (PTT), which involves the generation of heat under irradiation to achieve photothermal ablation of BC with minimal invasiveness and outstanding spatial–temporal selectivity, has been demonstrated as a novel therapy which can overcome the drawbacks of chemotherapy or surgery. Significantly, when combining PTT with chemotherapy and/or photodynamic therapy, an enhanced synergistic therapeutic effect can be achieved in both primary and metastatic BC tumors. Thus, this review discusses the recent developments in nanotechnology-based photothermal therapy for the treatment of BC and its metastasis to provide potential strategies for future BC treatment.